EFFECT OF FENCAMFAMINE ON AVOIDANCE PERFORMANCES OF RATS - Delucia, R.; Aizenstein, M. L.; Planeta, Cleopatra da Silva [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 1991)
The effects of fencamfamine (1.0 and 5.0 mg/kg, ip, single dose) on an inhibitory task were studied in rats (N = 15 per group). Post-training treatment with fencamfamine (1.0 mg/kg) significantly increased avoidance latency from 23 +/- 3 to 146 +/- 28 and 170 +/- 33 s for training day 1 and day 7, respectively, indicating an enhancement of retention. However, retention was significantly reduced with a high dose of fencamfamine (5.0 mg/kg). These results demonstrate that fencamfamine caused a reproducible dose-related increase and reduction in avoidance latency.
Keywords: FENCAMFAMINE; INHIBITORY AVOIDANCE; COGNITION